Project selection problem in R&D center by using fucom, Mairca & Knapsack algorithm - Karaçayır, Pınar (Graduate School, 2024)
Companies encounter numerous decision-making problems throughout the day to sustain their existence. Making correct decisions enables companies to sustain their existence profitably, while incorrect decisions negatively affect companies and threaten their existence. Therefore, companies must consider many criteria when making investment decisions. The purpose of this study is to develop an integrated quantitative approach to support decision-making processes by considering numerous conflicting criteria in evaluating and selecting various projects of businesses. The proposed approach consists of three stages. The first stage involves determining the criteria and weights to be used in the evaluation of projects, the second stage involves evaluating the projects according to the identified criteria and determining their weights, and the third stage involves selecting the projects to be invested in, taking into account various constraints of the business. The proposed model has been applied for the selection of R&D center projects that producing durable consumer goods. The criteria were determined by creating a hierarchical structure, taking into account opinions of experts in the company and the literature. In this context, four main criteria and their sub-criteria were considered, totalling nine criteria. The four main criteria are: economic, institutional, technological and strategic. In the first stage of the study, the Full Consistency Method (FUCOM), one of the Multi-Criteria Decision-Making model approaches, was used to determine the weights of the criteria. The main reasons for the application of this method are its emphasis on subjective judgments, a small number of comparisons, and consideration of consistency analysis during criterion comparisons. In determining the importance of the criteria, five experts were consulted. Since experts also considered linguistic variables when evaluating criteria, the weights of the criteria were also evaluated with the Fuzzy FUCOM. The aim of using Fuzzy FUCOM is also make comparisons of results obtained with two methods. At the end of the study, no significant difference was observed between the results of the Full Consistency Method and the Fuzzy Full Consistency Method. In the next stage, Multi-Attributive Ideal-Real Comparative Analysis (MAIRCA) method was used to create a ranking of alternatives. This method was preferred because it is used in problems with a large number of alternatives in the literature, and in this study, there were 17 alternative projects. As a result of the study, investment alternatives were ranked. In the final stage of the study, knapsack algorithm was created under various constraints and objectives to select the optimal projects for the company. The findings obtained serve as a guide for all R&D centers to achieve competitive advantage and improve complex decision-making processes.
Fucom, Mairca & Sırt Çantası algoritmasını kullanarak bir ar-ge merkezinde proje seçim problemi
Thesis (M.Sc.) -- İstanbul Technical University, Graduate School, 2024
Keywords: fuzzy logic; bulanık mantık; decision making; karar verme; Full Consistency Method (FUCOM)